A clinical study of anemia in children aged 6 months–5 years in a tertiary care center, Bengaluru, Karnataka, India - Saranappa, Siva; Wu, Jennifer (Indian Journal of Child Health, 2021)
Background: Anemia is the most commonly observed hematological diseases in children. The World Health Organization (WHO) has estimated that globally, 1.62 billion people are anemic, with the highest prevalence of anemia (47.4%) among preschool-aged children. Of these 293 million children, 89 million live in India. Aim: This study aims to evaluate the factors causing anemia in children aged between 6 months and 5 years and its prevalence within this age group. Methods: This study is a prospective observational study conducted in KIMS Hospital, Bengaluru, Karnataka. A total of 200 children in the age group of 6 months–5 years with features of anemia or having hemoglobin <11 g/dl were included in the study for a duration of 18 months between January 2019 and June 2020. Detailed history was recorded and examination findings were noted. The data collected were tabulated and statistically analyzed accordingly. Results: About 57.5% of the children with anemia fell between the age group of 6 months and 2 years and 42.5% of children were in the age groups of 2–5 years. A male predominance was seen (61%) with male-to-female ratio of approximately 1.56:1. Most of the children were found to have mild (46%) and moderate anemia (46%) with only a minority (8%) presenting with severe anemia. About 56.5% of the children had a normal nutritional status while 41% were malnourished and 2.5% had both wasting and stunting. Exclusive breastfeeding (for 6 months) history was present in 59% of the children. These children belonged mostly to the upper lower (45%) and lower middle (41%) socioeconomic status. This study also showed anemia in children most commonly presented majorly with concurrent involvement of the respiratory system (31%) followed by infectious diseases (30%) and gastrointestinal disorders (23%). Conclusion: The current study concludes that iron deficiency anemia is a multifactorial hematological disease. Learning about the predisposing risk factors can help to adopt the necessary precautions to prevent anemia in these children. Improving the nutritional status of the children by involving parents and counseling them regarding important feeding practices can help to prevent anemia.